Dialects, cultural Identity, and economic exchange - Oliver Falck; Stephan Heblich; Alfred Lameli; Jens Suedekum (Center for Economic Studies and ifo Institute (CESifo), 2010)
We investigate whether time-persistent cultural borders impede economic exchange across regions of the same country. To measure cultural differences we evaluate, for the first time in economics, linguistic micro-data about phonological and grammatical features of German dialects. These data are taken from a unique linguistic survey conducted between 1879 and 1888 in 45,000 schools. Matching this information to 439 current German regions, we construct a dialect similarity matrix. Using a gravity analysis, we show that current cross-regional migration is positively affected by historical dialect similarity. This suggests that cultural identities formed in the past still influence economic exchange today.
Keywords: R23; Z10; J61; 330; dialects; language; culture; internal migration; gravity; Germany; Interregionaler Handel; Binnenwanderung; Kulturpsychologie; Sprache; Gravitationsmodell; Schätzung; Deutschland